PERMAINAN - Totok Priyoleksono (SURYA SENI, 2008)
The Game.The process of art creation in general includes (a) to realize self-existence in life (culture); (b) to respond  the real life (local and global) as  a sculptor (artist); (c) to visualize the respose in an art work; (d) to realize the desire to communicate self  by the relevant means and ways; (e) to realize that visual objects  consist of a series of human signs that keep, process, and obtain meaningful information through  objective and subjective description; (f) to realize that each individual has different patterns of  social, political, and culturalgames.In particular, we seek possible types of game we commonly ﬁ nd to be combined with social, political, and cultural conﬂicts. The role of playing and being played among humans in the world is symbilized in the art work.This is an observativory and exploratory study. Observation was conducted to collect scientiﬁ c verbal and visual facts and information. The observed games and dynamics of humans are taken to be the idea of the sculpture. Exploratory method is employed to express possible visual symbols in sculpture.  It can be concluded that: (1) there are different ways and means of games in the society; (2) the games that people play are full of conﬂ icts; (3) the work of sculpture can be used to communicate the real games containing moral values ofhuman in a constructive way.Keywords: Games and Moral Values